Penerapan Metode Ekstrapolasi Nonlinear Dan Algoritma Wiener Pada Citra Blur (Deblur) - Dicky Purba (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
Image processing is an image processing and analysis process that has a lot of visual perception that has the characteristics of input data and output information in the form of images. An unfavorable image can be caused by many factors, including lack of sharpening, blur, and so on. Poor image quality of course will affect the information contained in the image. This of course resulted in the delivery of information on the image is not effective. For this reason, image improvement is needed. In this study, the author will apply the technique of improving the blurred image using the Nonlinear Extrapolation method and the Wiener filter. At first, the blurred image will be sharpened by using the Nonlinear Extrapolation method. Then the sharpened image will be corrected by using the Wiener algorithm. From the results of the experiment using the Nonlinear Extrapolation method, a better image was obtained by increasing the sharpening based on the high frequency of the image, namely by adding sharpening to the initial image. Then the sharpened image is corrected using the Wiener algorithm which produces an output image by correcting the blur that exists in the image.